Plastic recycling in Poland – a transformation towards a circular economy? - Baran, Bernadeta (Recykling tworzyw sztucznych w Polsce – transformacja w kierunku gospodarki cyrkularnej?)
Plastic is one of the world’s most-used materials. Unfortunately, its widespread use is also connected with a large amount of waste. The main challenge of modern economies, including Poland, is the transition into a circular economy, which aims to minimize the amount of waste generated and the use of unavoidable waste as resources through recycling processes. The aim of the article is to indicate the degree of Poland’s transformation in the area of plastic waste recycling. Poland produces less plastic waste than the EU15, but the level of recycling is lower than the EU average. The recycling of plastic waste is largely based on easy-to-collect waste from commercial networks and transport. A further increase in the recycling rate will be possible when the selective collection and recycling of household waste is intensified. Both campaigns promoting the ecological awareness of inhabitants and systemic actions aimed at increasing the degree of use of recyclable materials are necessary
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2021; vol. 65, nr 1, s. 1-10